Root-Derived Phytochemicals from Inula confertiflora for Antioxidant and Antibacterial Activities - Mohammad Budiyanto; Abere Habtamu Manayia; Esubalew Meku Godie; Minbale Gashu Tadesse; Fasih Bintang Ilhami; Sapti Puspitarini (Science and Technology Indonesia, 2026)
Inula confertiflora, a medicinal herb indigenous to Ethiopia, often used in traditional treatments for inflammatory and pain-related conditions. The root of I. confertiflora was soaked with n-hexane, ethyl ether, and acetone solvents. The proportion of crude extracts derived from ethyl ether extracts was 1.4 times higher than that of n-hexane and 1.2 times higher than that of acetone. Analytical detection results of crude extracts confirmed that I. confertiflora contained a variety of different preliminary phytochemicals. The higher concentrations of total flavonoids and other polar phytoconstituents present in the ethyl ether extracts were associated with greater radical-scavenging effectiveness in the DPPH solution. More than half of the bacterial growth efficiency was restricted by phytochemicals derived from I. confertiflora root extracts using non-polar, medium-polar, and high-polar solvents. It is crucial to note that medium-polar extracts of I. confertiflora root decreased the inhibitory effect on the development of both gram-positive and gram-negative bacterial strains at a concentration of 100 μg/mL using acetone as the solvent. Additionally, they exhibited improved radical scavenging against a DPPH solution. Moreover, molecular docking simulation clearly revealed that I. confertiflora extracts have a strong binding affinity toward four key bacterial target proteins (LasB (-7.9kcal/mol), PBP2a (-8.0kcal/mol), FabH (-11.3kcal/mol), and MurA1 (-4.7kcal/mol)). Collectively, these findings suggest that I. confertiflora extracts exhibit substantial potential as antibacterial agents by targeting diverse and functionally important bacterial proteins.